Enabling Urban Alternatives Crises, Contestation, and Cooperation - Fisker, Jens Kaae; Chiappini, Letizia; Pugalis, Lee; Bruzzese, Antonella (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
This book asks how thinking, governing, performing, and producing the urban differently can assist in enabling the creation of alternative urban futures. It is a timely response to the ongoing crises and pressing challenges that inhabitants of cities, towns, and villages worldwide are faced with in the midst of what has been widely dubbed as 'an urban age'. Starting from the premise that current urban development patterns are unsustainable in every sense of the word, the book explores how alternative patterns can be pursued by the wide variety of actors - from governments and international institutions to slum-dwellers and social movements - involved in the on-going production of our shared urban condition. The challenges addressed include exclusion and segregation; persisting poverty and increasing inequality; urban sprawl and changing land use patterns; and the spatial frames of urban policy. As such the book appeals to urban scholars, policy makers, activists, and others concerned with shaping the future of our cities and of urban life in general. Additionally, it is of interest to students in urban planning, architecture and design, human geography, urban sociology, and related fields.